1995
DOI: 10.1109/50.400677
|View full text |Cite
|
Sign up to set email alerts
|

High dynamic range temperature point sensor using green fluorescence intensity ratio in erbium-doped silica fiber

Abstract: We propose a sensor based on the temperature dependant behavior of the two lines of green emission of the erbium ion. The ratio of the intensities of these two lines presents a very low dependance on pump wavelength and pump power fluctuations. The sensitivity of the ratio is 0.013PC between room temperature and 600" C. In addition, the measurement is selfcalibrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0
6

Year Published

1997
1997
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(35 citation statements)
references
References 9 publications
1
28
0
6
Order By: Relevance
“…PA processes have proved to be useful in applications such as temperature sensors, 21,22 UC lasers, 23 laser cooling of solids, 24,25 and phase-conjugated mirrors. 26 It was also shown that the laser threshold of a fiber laser could be reduced as well as its output power enhanced using a PA excitation scheme.…”
Section: Introductionmentioning
confidence: 99%
“…PA processes have proved to be useful in applications such as temperature sensors, 21,22 UC lasers, 23 laser cooling of solids, 24,25 and phase-conjugated mirrors. 26 It was also shown that the laser threshold of a fiber laser could be reduced as well as its output power enhanced using a PA excitation scheme.…”
Section: Introductionmentioning
confidence: 99%
“…The change in refractive index is assumed to be negligible [10,15], since it is typically ten times smaller than the cavity expansion rate.…”
Section: Resultsmentioning
confidence: 99%
“…The main transition processes for Er:Yb phosphate glass pumped around 978 nm have been extensively described elsewhere [10,15,16]. Boltzmann statistics can be used to describe the strong thermal coupling and the population redistribution between the 2 H 11/2 and 4 S 3/2 erbium energy levels that lead to green emissions at 530 nm and 554 nm respectively on decay to the **** The largest measured 530:554 nm intensity ratio for IOG-2 is 3.5, equivalent to a temperature over 800 K [18].…”
Section: Resultsmentioning
confidence: 99%
“…флуоресценция с длиной волны, меньшей длины волны накачки, продемонстрирована для большинства редкоземельных элементов [1]. Интерес к этому явлению обусловлен возможностью его использования для преобразования частоты оптического излуче-ния в солнечных фотоэлементах [2] и фотовольтаических устройствах [3], дисплеях, сенсорах [4] и дру-гих устройствах, в микроскопии биологических объектов [5], а также для лазерной генерации [6,7]. Ак-туальным является исследование флуоресценции активаторов в различных материалах, в том числе в наноструктурированных [8,9].…”
Section: Introductionunclassified